COMPARABLE ANALYSIS OF TRAINING OPERATORS QUALITIES AMONG SWIMMERS OF MONTENEGRO AND VOJVODINA - Branislav Radulović; Kosta Goranović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
The structure and dynamics of the training process appear as one of the major components concerning all issues of how to achieve high results in swimming. One of the most important conditions of efficient implementation of sports training transformation process is its proper planning and programming. A great number of training operators that show the movement trend of training pressures can be sorted out and defined from an annual plan of a swimmer's training process. By determining the differences in the training process operators qualities among swimmers of Montenegro and Vojvodina, herewith the authors have tried to answer some questions concerning the submodel of dosing the global pressure volume and emphasizing its components (intensity, extent and frequency) in certain phases of ontogenetic development of a swimmer. A hypothetic model of training operators in the annual cycle of a swimmer is given here and it is assumed that it considerably effects smooth movement in water: extent and intensity of swimming, number of trainings, number of competitions, training time spent in water and training time spent on surface. Based on analysis of basic descriptive statistics of the training operators variables among swimmers of Montenegro, differences are evident in comparison to the so far made searches and experience. A significant statistic difference was noticed in a certain number of variables for different age groups in comparison with the swimmers from Vojvodina. Low qualities of certain training operators are especially evident for the teen-ager group and seniors in men, as well as pioneers and cadets in women competition.